Major Cognitive Changes and Micrographia following Globus Pallidus Infarct - Sarah Nelson; Hassanain Toma; Haley LaMonica; Tinatin Chabrashvili (Case Reports in Neurological Medicine)
Importance. Globus pallidus (GP) lesions are well known to cause motor deficits but are less commonly—and perhaps not conclusively—associated with cognitive problems. Observations. We present a 45-year-old male with no significant neurological or psychological problems who after suffering a GP infarct was subsequently found to have substantial cognitive problems and micrographia. Formal neuropsychological testing was not possible due to lack of patient follow-up. Conclusions and Relevance. Despite the conflicting literature on the association of GP lesions and cognitive deficits, our patient demonstrated significant neuropsychological changes following his stroke. In addition, evidence of micrographia likely adds to the literature on the localization of this finding. Our case thus suggests that neuropsychological testing may be beneficial after GP strokes.